Analysis of Beginning Stage of Reading Skills of First Grade Students of Indriasana Palembang Primary School. - Indriasari, Indriasari; Krisnandi, Ignasius Firdo (International Journal of Business, Law, and Education, 2023)
This study aims to describe the beginning stage reading ability of first grade students at SD Indriasana Palembang. This research method is descriptive qualitative, with data collection through observation, interviews, tests, and documentation. The sample used saturated sampling technique. The research sample was 61 first grade students at SD Indriasana Palembang. The results of the study, first in the aspect of reading letters as much as 98% of respondents achieved the criteria of "very good" and 2% achieved "good". Second, in the aspect of reading syllables, 98% of respondents with the criteria of "very good" and 2% "enough". Third, in the aspect of reading words 92% of respondents with the criteria of "very good" and 8% "enough". Fourth, in the aspect of reading sentences 84% ​​of respondents with "very good", 11% "good", and 5% "enough".